Basic Financial Management. - Vinso, Joseph D.; Martin, John D.; Petty, J. William; Keown, Arthur J.; Scott, David F. (Journal of Finance, 1981)
1. An Introduction to Financial Management.Appendix: Methods of Depreciation. 2. The Role of Financial Markets and Interest Rates in Financial Management. 3. Evaluating a Firms Financial Performance and Measuring Cash Flow. 4. Financial Forecasting, Planning, and Budgeting. 5. The Time Value of Money. 6. Risk and Rates of Return.Appendix: Measuring the Required Rate of Return: The Arbitrage Pricing Model. 7. Bond Valuation. 8. Stock Valuation.Appendix: The Relationship Between Value and Earnings. 9. Capital-Budgeting Decision Criteria. 10. Cash Flows and Other Topics in Capital Budgeting. 11. Capital Budgeting and Risk Analysis. 12. Cost of Capital. 13. Analysis and Impact of Leverage. 14. Planning the Firms Financing Mix. 15. Dividend Policy and Internal Financing. 16. Working-Capital Management and Short-Term Financing. 17. Cash and Marketable Securities Management.Appendix: Cash-Management Models: Split Between Cash and Near Cash. 18. Accounts Receivable, Inventory, and Total Quality Management. 19. Term Loans and Leases. 20. The Use of Futures, Options, and Currency Swaps to Reduce Risk.Appendix: Convertible Securities and Warrants. 21. Corporate Restructuring: Combinations and Divestitures. 22. International Business Finance. Appendix A: Using a Calculator. Appendix B: Compound Sum of $1. Appendix C: Present Value of $1. Appendix D: Sum of an Annuity of $1 for n Periods. Appendix E: Present Value of an Annuity of $1 for n Periods. Appendix F: Solutions for Selected End-of-Chapter Problems. Glossary. Organization Index. Subject Index.